Socio-Economic Determinants of Poverty in Southwest Papua Province: A Panel Data Analysis Using Fixed Effects Model (2014–2023) - Elina R Situmorang; Obadja A. Fenetiruma; La Ode Alisyah; Sufia Sifra Asrouw (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The poverty rate is one of the key indicators used to assess the welfare of communities within a region, as poverty issues are influenced by both social and economic factors. Objective: This study aims to examine poverty levels in Southwest Papua Province and analyze the effects of socio-economic factors on poverty levels in Southwest Papua Province. Methods: The data used consist of panel data covering the period from 2014 to 2023, including several regencies/cities in Southwest Papua Province. The analytical method employed is panel data regression using the Fixed Effects Model (FEM), which was selected based on model selection tests conducted using Stata 17 software. Results: The results indicate that the poverty rate in Southwest Papua Province is considerably higher than the national average, with a gap of approximately 7.51 percentage points in 2023. Based on the Fixed Effects Model with Cluster-Robust Standard Errors (R² = 0.8783; n = 60; F-prob = 0.0002), Average Years of Schooling (β = −3.345; p = 0.025) and Per Capita Expenditure (β = −0.001; p = 0.037) have negative and statistically significant effects on poverty rates, while Total Population, Open Unemployment Rate, and the Construction Cost Index have positive but statistically insignificant effects. Conclusion: These findings imply that local government policies aimed at improving the quality of education and enhancing people’s purchasing power may serve as effective strategies for reducing poverty rates. Additionally, efforts to control the unemployment rate and account for construction cost factors should be considered in economic development planning in Southwest Papua Province.